PENGARUH KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING: STUDI PADA FAKULTAS EKONOMI DAN BISNIS, UNIVERSITAS TABANAN - Ayu Wisudayanti; I Ketut Mustika (Journal of Applied Management Studies, 2021)
This study aims to identify and analyze the influence of leadership, work environment, job satisfaction on the performance of lecturers at the Faculty of Economics and Business, Tabanan University; identify and analyze the influence of leadership and work environment on the job satisfaction of lecturers at the Faculty of Economics and Business, Tabanan University; and identify and analyze the influence of leadership and work environment on performance through job satisfaction of lecturers at the Faculty of Economics and Business, Tabanan University. This study uses a quantitative approach that focuses on testing hypotheses using measured data and involving all 60 lecturers who teach at the Faculty of Economics and Business, Tabanan University. The data of this research are sourced from primary data and secondary data. The data collection method in this study used a questionnaire and documentation. The collected data were analyzed using validity and reliability tests with the help of SPSS for Windows version 22.0, description of research variables, classical assumption test (normality test, multicollinearity test, heteroscedasticity test, autocorrelation test), model fit testing, and path analysis. The results of this study shows that leadership has a positive and significant influence on lecturer performance, work environment has a positive and significant influence on lecturer performance, job satisfaction has a positive and significant influence on lecturer performance, leadership has a positive and significant direct influence on lecturer job satisfaction, work environment has a positive and significant influence directly on the job satisfaction of lecturers, leadership indirectly has a positive and significant influence on the performance of lecturers, leadership indirectly has a positive and significant influence on the performance of lecturers through job satisfaction, and the work environment indirectly have a positive and significant influence on lecturer performance through lecturer job satisfaction.